Performance evaluation of hybrid electrochemical processes in mature leachate treatment - Bilgin, Oyku Nur; Yokus, Senem; Varank, Gamze; Guvenc, Senem Yazici; Can-Guven, Emine; Demir, Ahmet (WILEY, 2023)
BACKGROUND: Recently, hybrid treatment applications have gained attention in the treatment of high-strength wastewater. In this study, the following hybrid applications were applied: electrocoagulation (EC)-electrooxidation (EO) (EC-EO), and EO-EC. The single EC and EO processes were independently optimized and then hybrid EC-EO and EO-EC processes were applied under the optimized conditions. Firstly, the most effective electrode pairs were selected in both EC and EO processes concerning pollutant elimination performance and energy needs. Afterward, the optimum values of the system requirements (initial pH, applied current, inter-electrode distance, and reaction time) of the EC and EO were determined.RESULTS: Al-Al in the EC process and a Ti/RuO2-graphite anode-cathode combination in the EO process were the most effective electrodes. Under optimum conditions (EC process: pH 7, applied current 2 A, reaction time 60 min, and inter-electrode distance 2 cm; EO process: pH 7, applied current 1 A, reaction time 120 min, and inter-electrode distance 2.5 cm), the chemical oxygen demand (COD) yields for EC and EO processes were 56.6% and 45.6%, respectively. The hybrid EC-EO and EO-EC processes yielded 69.6% and 66.4% COD removal, respectively. Specific energy consumption values for the EC, EO, EC-EO, and EO-EC were calculated as 14.1, 41.8, 38.9, and 40.7 kWh kg(-1) COD, respectively.CONCLUSION: Based on its pollutant removal efficiencies and energy usage values, the hybrid EC-EO process was found to provide significant advantages in mature leachate treatment. (c) 2023 Society of Chemical Industry (SCI).
Keywords: electrocoagulation; electrooxidation; hybrid treatment; mature leachate; specific energy consumption; WASTE-WATER TREATMENT; LANDFILL LEACHATE; SANITARY-LANDFILL; ELECTROOXIDATION TREATMENT; HUMIC-ACID; OXIDATION; WASTEWATERS; REMOVAL; DEGRADATION; Biotechnology & Applied Microbiology; Chemistry; Engineering